Treatment of Rhinitis Sicca Anterior with Ectoine Containing Nasal Spray. (12th April 2014) - Sonnemann, Uwe; Scherner, Olaf; Werkhäuser, Nina
Abstract : Objectives. The safety and efficacy of ectoine nasal spray and ectoine nasal spray with dexpanthenol in the treatment of rhinitis sicca were evaluated in two studies. Design and Methods. Two noninterventional observational studies were performed to evaluate the efficacy and safety of a nasal spray containing ectoine (study 1) and ectoine/dexpanthenol (study 2) over a period of two weeks including comparable numbers of patients suffering from rhinitis sicca anterior. Patients and physicians were asked to rate the efficacy in reducing symptoms and the tolerability over the treatment phase. Results. The treatment in both studies resulted in a clinical and statistical significant reduction of the main diagnosis parameters, nasal airway obstruction, and crust formation. There was also a significant reduction in the secondary diagnosis parameters in both studies. Importantly, the tolerability was very good. During the whole observational study, neither patients nor doctors stopped the medication due to unwanted effects. Conclusion. Rhinitis sicca could be successfully treated with a nasal spray containing ectoine and a nasal spray combining ectoine with dexpanthenol. The combination of both substances led to slight advantages.